Europe's mining innovation trends and their contribution to the sustainable development goals: Blind spots and strong points. (December 2021) - Endl, Andreas; Tost, Michael; Hitch, Michael; Moser, Peter; Feiel, Susanne
Abstract: For millennia, mining was not only a source of great economic wealth, but also of social and environmental concern. It, therefore, was a focus of the business and public policy sustainable development agenda for many years. Thus, many international programmes, such as the International Council on Mining & Metals (ICMM) and the United Nations Development Programme (UNDP), tried to capture this concept by developing frameworks to guide in their implementation by the mining sector. However, there is scarce knowledge about the mining sector's contribution to the UN Sustainable Development Goals (SDGs) - the broadly accepted and politically legitimised post-2015 development agenda. This paper investigates the extent to which mining innovations that are employed, or that will be employed in the future, can make a contribution to achieving the SDGs in Europe. To this end, the authors identified current and future mining Innovation Concepts and challenges, as well as designed an SDG impact framework for identifying the impacts of innovation, concluding that almost all innovation concepts show repercussions on individual SDGs. This indicates that innovation concepts not only depict synergies between the SDGS, but also trade-offs or imbalances between individual SDGs. Further research is required on the overall environmental impact of technological innovations, the implications for absolute de-coupling of environmental impacts and economic performance, and the possibility of rebound effects. Highlights: Identification of current and future Innovation Concepts for extraction in Europe. Despite positive aspects most innovations indicate trade-offs with other SDGs. The economically driven technological innovations change the societal contract. Innovations do not contribute to SDG 5 on gender equality.